THE LEGAL TRADITION IN INDONESIA: FINDING THE MIDDLE WAY - Maghfirah Maghfirah; Zulkifli Zulkifli; Muhammad Alpi Syahrin; Aslati Aslati (Sosiohumaniora, 2022)
Community life continues to develop dynamically. Along with that, various demands emerged to make various changes towards the achievement of national goals. Changes to the framework of the national legal system that was built on the basis of Pancasila and the 1945 Constitution. The direction of development must take into account the plurality of society without limiting rights and giving respect to the implementation of the law without overriding other legal interests. The context of a pluralistic Indonesian society develops along with the dynamics and development of society, both socio-culturally and politically. This article discusses the legal tradition that grows and takes root in Indonesia. This article is a normative research, which is conducting a literature study or secondary data to collect data through documentation from various articles, books, and other sources that discuss legal traditions in Indonesia. The finding of this article is that legal practices that develop in Indonesia are customary law, Islamic law, and Continental Europe. In the development of national law through the “middle way” as a principle of compromise against legal traditions that influence and attract each other, taking into account the philosophical, sociological, and juridical. In essence, legal practice refers to welfare and benefit considerations: “maintaining old traditions that are still relevant, building new, better traditions.” What this article has in common with others is that it discusses legal traditions, while the difference is that this article analyzes the development of legal practice in Indonesia from various perspectives and approaches to religious values so as to create a just legal concept.